Petroglyphs of church of Matara, Antabamba-Apurímac - Carreño-Collatupa, Raúl (2021)
Nine petroglyphs were identified on a stairway located in the access arch to the Matara ecclesiastical complex, Antabamba province, Apurimac, all of them containing abstract figurations engraved on the andesitic rock. Due to the nature of its iconography, the fact that pre-inka engravings cut as ashlars, incorporated to an Inka structure (huaka = shrine) and, subsequently, to a colonial ecclesiastical complex, it is undeniable that these petroglyphs are pre-inka belonging to a secondary context. As far as it is known, they are the first petroglyphs registered in Antabamba province, where only pictographs were previously known. Unfortunately, most of them have disappeared in recent years due to a wrong ‘modernization’ concept undertaken by the municipal authorities of Matara and Huaquirca.